DEVELOPMENT OF PROBLEM-BASED LEARNING-BASED E-MODULES WITH FLIP PDF PRO APPLICATION IN PHYSICS COURSES - Afifah Hidayatullah; Silvi Trisna; Aidhia Rahmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper is based on the lack of students' learning interest in physics courses, which is indicated by the teaching materials used by educators during the learning process. The research in this paper aims to develop problem-based learning of e-glasses modules on momentum and impulse material as well as to determine the validity and practicality of e-modules for students of class X at SMA Negeri 1 Tapung. The type of research is the research and development (R&D) method. The method used is an R&D panel with the ADDIE model. To achieve the goal, several stages of development are analyzing, designing, developing, implementing, and evaluating. In addition, the research result is an electronic module on momentum and impulse material. The validation results of material and media experts on the electronic module achieve a proportion of 81.86%, which is in the very valid category. The practicality of a product seen from the practicality test that was obtained from the results of the practicality sheet for the electronic module is 95.70% and categorized in the very practical category.